Heparin binding confers prion stability and impairs its aggregation. Issue 6 (19th March 2014) - Vieira, Tuane C. R. G.; Cordeiro, Yraima; Caughey, Byron; Silva, Jerson L.
ABSTRACT: The conversion of the prion protein (PrP) into scrapie PrP (PrP Sc ) is a central event in prion diseases. Several molecules work as cofactors in the conversion process, including glycosaminoglycans (GAGs). GAGs exhibit a paradoxical effect, as they convert PrP into protease‐resistant PrP (PrP‐res) but also exert protective activity. We compared the stability and aggregation propensity of PrP and the heparin‐PrP complex through the application of different in vitro aggregation approaches, including real‐time quaking‐induced conversion (RT‐QuIC). Transmissible spongiform encephalopathy–associated forms from mouse and hamster brain homogenates were used to seed RT‐QuIC‐induced fibrillization. In our study, interaction between heparin and cellular PrP (PrP C ) increased thermal PrP stability, leading to an 8‐fold decrease in temperature‐induced aggregation. The interaction of low‐molecular‐weight heparin (LMWHep) with the PrP N‐ or C‐terminal domain affected not only the extent of PrP fibrillization but also its kinetics, lowering the reaction rate constant from 1.04 to 0.29 s –1 and increasing the lag phase from 12 to 19 h in RT‐QuIC experiments. Our findings explain the protective effect of heparin in different models of prion and prion‐like neurodegenerative diseases and establish the groundwork for the development of therapeutic strategies based on GAGs.—Vieira, T. C. R. G., Cordeiro, Y., Caughey, B., Silva, J. L. Heparin binding confers prion stability and impairs its aggregation. FASEB J . 28, 2667–2676 (2014). www.fasebj.org